2005
DOI: 10.1111/j.1365-3083.2005.01656.x
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Cytokine‐Suppressive CD4+CD25+ T Cells in the Peripheral Blood and Synovial Fluid of Patients with Rheumatoid Arthritis

Abstract: CD4þ CD25 þ T cells have been shown to play a regulatory or suppressive role in the immune response and are possibly relevant to the pathogenesis of autoimmune diseases. In the present study, we attempted to investigate the levels of CD4 þ CD25 þ T cells in the peripheral blood (PB) and synovial fluid (SF) of patients with rheumatoid arthritis (RA) and the effects of CD4 þ CD25þ T cells on the in vitro cytokine production by stimulated SF mononuclear cells (SFMC). The results showed that RA patients had simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
1
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 32 publications
(38 reference statements)
7
36
1
9
Order By: Relevance
“…It is widely accepted that the frequency and the suppressor potency of CD4 ϩ CD25ϩ Treg found in the synovial fluid of RA patients are significantly elevated when compared with peripheral blood (25,(53)(54)(55)(56), and our results are consistent with previous observations. A question that has been asked by several investigators (25,53,54) is why an active joint inflammation persists in RA despite the presence of elevated frequencies of CD4 ϩ CD25 ϩ T cells with an enhanced suppressive capacity.…”
Section: Cd25supporting
confidence: 83%
“…It is widely accepted that the frequency and the suppressor potency of CD4 ϩ CD25ϩ Treg found in the synovial fluid of RA patients are significantly elevated when compared with peripheral blood (25,(53)(54)(55)(56), and our results are consistent with previous observations. A question that has been asked by several investigators (25,53,54) is why an active joint inflammation persists in RA despite the presence of elevated frequencies of CD4 ϩ CD25 ϩ T cells with an enhanced suppressive capacity.…”
Section: Cd25supporting
confidence: 83%
“…In agreement with these findings, the interaction of CD4 ϩ CD25 ϩ Treg cells with activated monocytes in the joint of RA patients might lead to diminished suppressive activity of Treg cells in vivo, thus contributing to the chronic inflammation in RA (25). With these results in mind, and the fact that the blockade of TNF-␣ by therapy with anti-TNF has proven to be beneficial by inhibiting inflammation and preventing joint damage in RA patients, one may assume that this clinical effect might be mediated in part by a restoration of the defective function of CD4 ϩ CD25 ϩ Treg cells in patients with active RA.…”
Section: Cd25supporting
confidence: 73%
“…47 Autoimmun Since phenotypic characterization does not allow a definite conclusion as to whether expanded CD4 + CD25 high T cells in the SF are actually Treg, the most convincing evidence is undoubtedly provided by in vitro functional studies. Suppressive activity of CD4 + CD25 high T cells in the SF has been confirmed in some studies by coculture with autologous effector T cells [33][34][35][36][37][38][39]. In contrast, some authors have demonstrated a reduced suppressive activity of Treg cells in PB from RA patients, that can be restored by adequate pharmacological therapy, as discussed in detail below (see Table 2).…”
Section: The Paradox Of Treg Cell Expansion In Ra Patientsmentioning
confidence: 88%